Potential of Market Development of Products and Marketing Strategies of Wood Crafts in Tegalalang Village, Gianyar Regency to Global Direction - Dewa Ayu Mei Arta Dewi; I Wayan Gede Suparta; Ni Luh Putu Indiani (Universitas Warmadewa, 2019)
The industrial sector is one of the main sectors as an engine driving economy in Bali. Seeing the potential of small industry is very good, does not mean in the business process does not face obstacles and challenges. The aims of research is to identify the strengths, weaknesses, opportunities and threats in the product market and to know the strategy of developing the wooden product market in Tegalalang village towards the Global. This research is explorative and the analytical tool used to compile the strategy factors is Matriks SWOT, while the method used in this research is qualitative. The samples are some craftsmen/Managers, wood farmers, and employees/worker shop owned by craftsmen. The total number of samples selected as informants is 10 people. The results of the research show that from IFAS / EFAS Matrix has been determined the number of IFAS score is 2.137 and EFAS score is 2.088. From these results it is known that the business position of the craftsmen in Tegalalang Village is currently located in cell V (five), which is in the Growth Stability Strategy (Growth Stability) which is the business growth of the craftsmen in Tegalalang Village, Gianyar Regency.